Ginger beer derived from back-slopping: Volatile compounds, microbial communities on activation and fermentation, metabolites and sensory characteristics - Iara Gomes de Oliveira, Louise; Karoline Almeida da Costa, Whyara; de Candido de Oliveira, Fernanda; França Bezerril, Fabrícia; Priscila Alves Maciel Eireli, Luana; dos Santos Lima, Marcos; Fontes Noronha, Melline; Cabral, Lucélia [UNESP]; Wagner, Roger; Colombo Pimentel, Tatiana; Magnani, Marciane (Elsevier, 2024)
Physicochemical parameters, microbial diversity using sequencing and amplicon, and metabolite concentrations from Ginger Bug and Ginger Beer were characterized. Furthermore, the sensory aspects of the beverage were determined. The longer ginger bug activation time (96 h) resulted in higher production of organic acids and alcohols, increased phenolic and volatile compounds concentration, greater microbial diversity, and increased lactic acid bacteria and yeasts. In the same way, the longer fermentation time (14 days) of ginger beer resulted in higher ethanol content, volatile compounds, and phenolic compounds, in addition to better sensory characteristics. Our results showed that ginger beer produced with ginger bug and fermented for 14 days showed better volatile and phenolic compound profiles, physicochemical parameters, microbial diversity, and sensory characteristics.
Keywords: Bacterial diversity; Fermented beverages; Ginger ale; Ginger bug; Zingiber officinale Roscoe